Pengelolaan Limbah Minyak Jelantah untuk Hidup Sehat dan Peningkatan Ekonomi Desa Muara - Louis Utama; Daffandra Artha Firdausy; Mudita Hung Dharma Putri; Joy Franklyn Liem Rustandi; Christian Wijaya (Prima Abdika: Jurnal Pengabdian Masyarakat, 2026)
Community service activities on healthy living, counseling, and the processing of used cooking oil waste were provided to residents of Muara Village, Teluk Naga District, Tangerang Regency, Banten Province. This is due to a lack of knowledge about healthy living and the use of cooking oil, and to the impact of used cooking oil waste, which can pollute the environment. Therefore, the method used is counseling to provide knowledge that used cooking oil waste can be properly managed by partners. Activities to overcome partner problems, namely the lack of knowledge about healthy living, including how to use cooking oil and dispose of used cooking oil waste without causing environmental pollution, can increase income for partner households. The activity was held in three stages, namely the first stage of a preliminary survey to determine the condition of partners and coordination with used cooking oil waste collectors for waste collection techniques, the second stage is to provide counseling to partners to provide knowledge about healthy living and how to manage used cooking oil waste so as not to pollute the environment and can increase partner household income and the third stage is an evaluation of the counseling provided. The aim of this activity is to enable partners to live healthy lives by using cooking oil in their daily lives, to manage used cooking oil waste so that it does not pollute the environment in accordance with sustainable principles, and to increase the income of partner households.